(untitled) (Linguistics in Amsterdam, 2011)
Sign language typology is a fairly new research field and typological classifications have yet to be established. For spoken languages, theseclassifications are generally based on typological parameters; it would thus be desirable to establish these for sign languages. In this paper, different typological aspects of sign languages are described. With respect to their potential contribution towards a typological classification, data from Inuit Sign Language regarding verb agreement and classifiers will be considered. We will suggest two classifications based on these morphosyntactic parameters.